2013
DOI: 10.1590/s1679-45082013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Evolução clínica de pacientes com mediastinite pós-cirurgia de revascularização miocárdica submetidos à oxigenoterapia hiperbárica como terapia adjuvante

Abstract: Objective:To evaluate the use of hyperbaric oxygen therapy as an adjunctive treatment in mediastinitis after coronary artery bypass surgery.Methods:This is a retrospective descriptive study, performed between October 2010 and February 2012. Hyperbaric oxygen therapy was indicated in difficult clinical management cases despite antibiotic therapy.Results:We identified 18 patients with mediastinitis during the study period. Thirty three microorganisms were isolated, and polymicrobial infection was present in 11 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…The incidence of postoperative DSWJ after cardiac surgery is rather low and ranges from 0.5% to 5.3% [ 1 4 , 11 , 12 ]. However, DSWI is one of the most serious complications, significantly increasing postoperative mortality, morbidity, time of hospitalization, hospital costs and need for surgical re-intervention [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of postoperative DSWJ after cardiac surgery is rather low and ranges from 0.5% to 5.3% [ 1 4 , 11 , 12 ]. However, DSWI is one of the most serious complications, significantly increasing postoperative mortality, morbidity, time of hospitalization, hospital costs and need for surgical re-intervention [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current paradigms in the management of sternal wound infection include surgical debridement, vacuum-assisted closure therapy, flap coverage, and sternal plating [ 18 ]. Unfortunately, in the available literature there is still insufficient information about hyperbaric oxygen therapy as an alternative treatment option in DSWI [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental rat model found that tigecycline was significantly superior to vancomycin in this application [ 15 ] . HBO has become a focus of interest for mediastinitis treatment in recent years; however, the patient numbers in both experimental and prospective randomised studies are insufficient [ 16 ] .…”
Section: Introductionmentioning
confidence: 99%